2022
DOI: 10.3389/fcell.2022.903696
|View full text |Cite
|
Sign up to set email alerts
|

The Desmosome-Keratin Scaffold Integrates ErbB Family and Mechanical Signaling to Polarize Epidermal Structure and Function

Abstract: While classic cadherin-actin connections in adherens junctions (AJs) have ancient origins, intermediate filament (IF) linkages with desmosomal cadherins arose in vertebrate organisms. In this mini-review, we discuss how overlaying the IF-desmosome network onto the existing cadherin-actin network provided new opportunities to coordinate tissue mechanics with the positioning and function of chemical signaling mediators in the ErbB family of receptor tyrosine kinases. We focus in particular on the complex multi-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In normal human skin, classical and desmosomal cadherins are differentially expressed in different layers of the epidermis. E-cadherin is present in almost all layers while desmoglein-1 is dominant in upper layers and desmoglein-3 in lower layers 19 , 20 . Our focus was on the fluorescence signal intensity of Alexa-488-labeled E-cadherin and desmoglein-1 in the upper layers of the pustulo-vesicle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In normal human skin, classical and desmosomal cadherins are differentially expressed in different layers of the epidermis. E-cadherin is present in almost all layers while desmoglein-1 is dominant in upper layers and desmoglein-3 in lower layers 19 , 20 . Our focus was on the fluorescence signal intensity of Alexa-488-labeled E-cadherin and desmoglein-1 in the upper layers of the pustulo-vesicle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Keratin-19 is a basic, type-I Keratin that is part of the Keratin-Desmosome scaffold 33 and which provides structural integrity to epithelial cells. It is possible then that the loss of Keratin-19 in Vangl2 S464N mutant bile ducts is due to disruption of intermediate filament formation secondary to desmosome disruption.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, when we quantify the differences between Keratin-19 positive bile ducts at E17.5 and E18.5 in Vangl2 +/+ compared to Vangl2 S464N animals we found that while there are similar numbers of bile ducts between the two genotypes at E17.5 there is a substantial reduction in bile duct number by E18.5 (Figure 3D and 3E) and the number of Keratin-19 positive cells within those bile ducts is also significantly reduced (Figure 3F). Keratin-19 is a basic, type-I Keratin that is part of the Keratin-Desmosome scaffold 33 and which provides structural integrity to epithelial cells. It is possible then that the loss of Keratin-19 in Vangl2 S464N mutant bile ducts is due to disruption of intermediate filament formation secondary to desmosome disruption.…”
Section: Vangl2 Interacts With Cell-cell Junction Proteins In Becs To...mentioning
confidence: 99%
“…The mechanical force from the ECM must be transmitted to the nucleus and, hence, participate in the phosphorylation of lamin A/C [49,58]. Mechanical signals are transduced to receptor tyrosine kinases in the ErbB family, contributing to the activities of the ErbB family [27]. Once activated, ErbB4 is capable of activating multiple kinases, including Akt1, MAPK, and PI3K [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, the soluble intracellular domain of ErbB4 translocates to the nucleus and modulates nuclear signaling 26 . The ERBB family also converts mechanical stimuli in the microenvironment into biochemical signals that promote tumor progression 27 . However, it is not clear whether ErbB4 can directly alter the mechanotransduction and nuclear structures.…”
Section: Introductionmentioning
confidence: 99%